ANALISIS KEKURANGAN DAN KELEBIHAN DARI USAHA SARANG BURUNG WALET DI KELURAHAN ANGSAU KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Benyamin Wahyudi Warisman; Wahyuni Ilham; Asysyifa Asysyifa (Jurnal Sylva Scienteae, 2020)
Swallow's nest is one of the Non-Timber Forest Products which has a high selling value.We need to know how the advantages and disadvantages of swallow nest business.This study aims to describe the advantages and disadvantages of the swallow nest business in Angsau Village, Tanah Laut Regency.The data consists of primary data obtained from direct interviews with building owners and special builders of swallow nest buildings and local communities involved in swallow nest business, which understands the problem of swallow birds.Data were analyzed using the SWOT method. The results of the study are the internal factors, namely the strengths of the swallow's nest business, which are locations for building swallow nests that have a spread of white swallow populations, high selling points and easy marketing channels.TheWeakness, high production and capital costs and unclear permits.The external factor namely Opportunity from swallow's nest business, namely the price classification so that all forms of nests can be sold, high export market demand, and technological progress, as well as the availability of artificial feed.Threats of this business are high land prices and the cost of building nests, rampant nest theft rates and predatory bird attacks, volatile exchange rates, and wrong harvesting methods.Keywords: Swallow's nest; advantages; disadvantages; opportunities; threats